Caracterização, germinação de sementes e desenvolvimento pós-seminal de Sapindus saponaria L - Neves, Maria Inajal Rodrigues da Silva das (2018)
The objective of this work was to characterize morphometrically saponaria (Sapindus saponaria L.) seeds; to extract and to quantify oil content, establish the percent composition of fatty acids; to describe their different post-seminal stages; to study their physiological behavior under treatments to overcome dormancy; temperature, light quality and standard methodologies for the tetrazolium and electrical conductivity tests. After saponaria seeds were harvested, the water content and the biometric measurements (length and width) were determined. The extraction and quantification of the seed oil was obtained by the solvent extraction method using the Soxhlet extractor system. Regarding the post-seminal development, the various processes triggered during the growth and development of the seedlings were evaluated. The treatments to overcome dormancy were: mechanical scarification, chemical scarification with sulfuric acid for 5, 10, 20, 30 and 40 minutes, immersion in hot water (80 ºC) until reaching room temperature, immersion in distilled water at room temperature for 24 hours and intact seeds (control). After this stage, the seeds were incubated at temperatures of 10, 15, 20, 25, 30, 35 and 40 ºC and alternated at 20-30 ºC under white light. The best light conditions were also established for germination and vigor test. For this purpose, the following light qualities were studied: white, red, red-distant and dark, at constant temperature 30 °C and alternating 20-30 °C. In the evaluation of the viability of S. saponaria seeds by the tetrazolium test, seeds were immersed in sulfuric acid for 30 minutes and submitted to pre-moistening for 24 hours at 30 °C, and then placed in 0.075% tetrazolium solution, 0.075%, 1%, 0.5% and 1.0% for 2, 4 and 6 hours at temperature of 30 °C. To evaluate the electrical conductivity of the seeds exudates present in the soaking solution (75 mL of deionized water), seeds were submitted to different soaking times (24, 48, 72 and 96 hours). The experimental design was completely randomized with a descriptive analysis of the biometric data and for the test of light quality at different temperatures the treatments were distributed in a factorial scheme. For the tetrazolium test, the 4 x 3 + 1 factorial arrangement was used, consisting of the combinations of four concentrations of the tetrazolium solution, three staining periods plus one control (germination test). The seeds had 17% initial moisture and the weight of 1.000 seeds was on average 672.4 g. Seeds dimensions, on average, was 10.3 mm long and 10,2 mm wide. The oil content found in the seeds was 7.25%, most of which was composed of unsaturated fatty acids (78.9%). The germination of S. saponaria seeds is hypogean type and the seedlings are cryptocoledonar. The highest germination values occurred when the seeds were immersed in sulfuric acid for 30 minutes. Seeds are preferentialy photoblasts positive, and presented higher values of percentage and germination speed when submitted to the temperature of 30 ºC. The concentration of 0.075% tetrazolium salt for four hours at 30 °C is an efficient combination for evaluating the viability of S. saponaria seeds. The highest leaching time occurred at 86 hours of imbibition.